NATIONALISM THROUGH GENERATIONS IN JHUMPA LAHIRI'S THE NAMESAKE - Alysia Shofi Nabila Puteri; Imas Istiani (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
National identity is a part of one’s self constructed by experience, memory, and cultural surroundings. This study explores how two generations of Indian immigrants express their nationalism in Jhumpa Lahiri's The Namesake. Using a postcolonial lens, this study applies Benedict Anderson's theory of imagined communities to examine the first-generation immigrants, Ashoke and Ashima, who maintain strong emotional ties to India by preserving Indian culture through food, clothing, language, habits, rituals, and resisting aspects of American customs. Meanwhile, their children, Gogol and Sonia, represent the second-generation immigrants who grew up in the United States and adopted American lifestyles. Their nationalism appears in more subtle and unconscious ways, more like Americans in terms of food preferences, habits, and holiday celebrations. Upon analysis, it was found that Gogol and Sonia did not wholly abandon their roots, as they persisted in Indian traditions such as wearing traditional attire and following a mourning diet ritual. Michael Billig's concept of banal nationalism is used to analyze how this generation blends American influence with selective participation in Indian customs. The study shows that nationalism can still be expressed abroad and does not have to be shown through overt or political acts.